وائل حلاق کی کتاب’’ناممکن ریاست‘‘ کا تنقیدی وتجزیاتی مطالعہ: A CRITICAL AND ANALYTICAL STUDY OF WAEL HALLAQ’S BOOK “IMPOSSIBLE STATE” - Abdul Basit; Javed Iqbal; Sadia Shabbir (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Wael B. Hallaq is a famous Scholar of the twentieth century. He was born in Nazareth, Palestine in 1955. He is an expert in Islamic Law. He did his Ph.D. at the USA, University of Washington. He served as Assistant Professor at McGill University and taught Islamic Law. He was promoted to Professor of Islamic law in 2005 at McGill University. He is one of the leading scholars of Islamic Law. Hallaq’s work has been widely debated and translated into Arabic, Hebrew, Indonesian, Italian, Japanese, Persian and Turkish, among others. His books and articles are a big source of knowledge to understand the oriental approach to Sharia. He has two points of view on Islamic law. In the first case, for the development of Islamic law, we must take historical, gradual, and evolutionary concepts into account. He broadly concurs with western philosophers in this aspect. This first component of Hallaq’s theories’ may be renamed as the theory of evolution of Islamic law. From the second point of view, Hallaq reviews how politics has affected Islamic law and daily life in the modern state and argues that this relationship between Islamic law and the modern state calls for moral philosophy to construct an Islamic state in the modern world. Without moral and ethical change in modern state, the development of Islamic state is Impossible in the world. Therefore, he called a Muslim state as impossible state to exist in modern world. There is also a disagreement with the proposed philosophy of Hallaq in view of the relationship between the modern state and Islamic law. Because Hallaq’s moral philosophy is basically a secular worldview. We have discussed second point of view oh Hallaq’s ideology in this paper.